Dopamine D2 receptor controls hilar mossy cells excitability. Issue 7 (9th May 2014) - Etter, Guillaume; Krezel, Wojciech
ABSTRACT Hippocampal control of memory formation is regulated by dopaminergic signaling. Whereas the role of dopamine D1 receptors is well documented in such regulations, functions of dopamine D2 receptors (DRD2) are not fully understood. Using fluorescence in situ hybridization we demonstrate that Drd2 expression in the hippocampus of wild‐type mice is limited to glutamatergic hilar mossy cells. Using whole cell electrophysiological recordings in hippocampal slice preparations, we provide evidence that unlike in basal ganglia, activation of DRD2 by the selective agonist, quinpirole, induces a long‐lasting increase in excitability of hilar mossy cells, which can be blocked by the DRD2 antagonist raclopride. Such activity is mediated by the Akt/GSK pathway, as application of specific inhibitors such as A1070722 or SB216763 prevented quinpirole activity. Long‐term effects of acute DRD2 activation in vitro suggest that volume transmission of dopamine may modulate mossy cell activities in vivo. This is supported by the presence of dense tyrosine hydroxylase positive varicosities in the hilus, which are rarely seen in the vicinity of mossy cell dendrites. From these data we discuss how dopamine could control mossy cell activity and thus dentate gyrus functions. © 2014 Wiley Periodicals, Inc.